Relations Between Religion And Science: A Critical Study Of Ahmad Baiquni's Interconnections In Educational Institutions - Rinda Fauzian; Yayat Hidayat; Saehudin; Nurhasan (Risâlah Jurnal Pendidikan dan Studi Islam, 2024)
Maintaining scientific traditions is part of civilization that must be maintained for generations. The relationship between religion and science is very close. Interestingly, Ahmad Baiquni was able to integrate and interconnect religion (Islam) with science. The purpose of this study is to critically analyze Ahmad Baiquni's views on the integration-interconnection of religion with science. The research method used is library research. The results showed that the integration and interaction of religion with science known as Islamic science is by linking the verses of the Qur'an to science and technology, especially science with the pattern of Islamization of science, the pattern of justification and sacralization. Ahmad Baiquni certainly views the relationship between religion and science as an Islamization that must always be massive. This is viewed as the thought of Islamization of knowledge that he synthesized is the Islamization of knowledge into two variants, namely the justification variant and the sacralization variant. Although the above-mentioned integrations have been completed, the facts on the ground are still needed and in reality, there are only a few who apply interconnections in various aspects. The interconnections of religion and science are part of the complex of educational problem solvers of yesterday, today, and the future.